Boundary Control as Gatekeeping in Facebook Groups - Sanna Malinen (Media and Communication, 2021)
Facebook groups host user-created communities on Facebook’s global platform, and their administrative structure consists of members, volunteer moderators, and governance mechanisms developed by the platform itself. This study presents the viewpoints of volunteers who moderate groups on Facebook that are dedicated to political discussion. It sheds light on how they enact their day-to-day moderation work, from platform administration to group membership, while acknowledging the demands that come from both these tasks. As volunteer moderators make key decisions about content, their work significantly shapes public discussion in their groups. Using data obtained from 15 face-to-face interviews, this qualitative study sheds light on volunteer moderation as a means of media control in complex digital networks. The findings show that moderation concerns not just the removal of content or contacts but, most importantly, it is about protecting group norms by controlling who has the access to the group. Facebook’s volunteer moderators have power not only to guide discussion but, above all, to decide who can participate in it, which makes them important gatekeepers of the digital public sphere.